Design of Multi-point Monitoring System Based on Internet of Things. Issue 4 (June 2019) - Qu, Na
Abstract: In recent years, due to the rapid development of Internet of Things technology, the online monitoring technology of electrical equipment has a new research direction. This design gives typical temperature/humidity, sound and light alarm, flammable gas and other monitoring and control system solutions for typical buildings such as teaching buildings, laboratory buildings, office buildings, dormitory areas, canteens, etc. on campus, and puts monitoring points into the sensor network. Then, the data is transmitted to the base station by wireless transmission, and then transmitted to the center via the base station, and the real-time monitoring function and the linkage alarm function can be realized in the terminal through the temperature management software. This design reduces the labor intensity of employees and reduces troubleshooting time.